Impacts of Priming with Silicon on the Growth and Tolerance of Maize Plants to Alkaline Stress - Abdel Latef, Arafat A.; Tran, Lam-Son P. (Frontiers in Plant Science, 2016)
Silicon (Si) has been known to augment plant defense against biotic and abiotic pressures. Maize (Zea maize L.) is classified as a Si accumulator and is relatively susceptible to alkaline stress. In this work, grains of maize were grown in pots and exposed to various concentrations of Na2CO3 (0, 25, 50 and 75 mM) with or without 1.5 mM Si in the form of sodium metasilicate Na2O3Si.5H2O for 25 days. Alkaline-stressed plants showed a decrease in growth parameters, leaf relative water content (LRWC), and the contents of photosynthetic pigments, soluble sugars, total phenols and potassium ion (K+), as well as potassium/sodium ion (K+/Na+) ratio. By contrast, alkaline stress increased the contents of soluble proteins, total free amino acids, proline, Na+ and malondialdehyde (MDA), as well as the activities of superoxide dismutase (SOD), catalase (CAT) and peroxidase (POD) in stressed plants. On the other hand, application of Si by grain priming improved growth of stressed plants, which was accompanied by the enhancement in LRWC, levels of photosynthetic pigments, soluble sugars, soluble proteins, total free amino acids, K+ and activities of SOD, CAT and POD enzymes. Furthermore, Si supplement resulted in a decrease in the contents of proline, MDA and Na+, which together with enhanced K+ level led to a favorable adjustment of K+/Na+ ratio, in stressed plants relative to plants treated with alkaline stress alone. Taken together, these results indicate that Si plays a pivotal role in alleviating the negative effects of alkaline stress on the maize growth by improving water status, enhancing photosynthetic pigments, accumulating osmoprotectants rather than proline, activating the antioxidant machinery, and maintaining the balance of K+/Na+. Thus, our findings demonstrate that seed priming with Si is an efficient strategy that can be used to boost tolerance of maize plants to alkaline stress.